Physical Compatibility and Chemical Stability of Fentanyl and Naloxone Hydrochloride in 0.9% Sodium Chloride Injection Solution for Patient-Controlled Analgesia Administration - Chen P; Chen F; Lei J; Zhou B (Dove Medical Press, 2020)
Peng Chen,1,* Fuchao Chen,2,* Jiexin Lei,3 Benhong Zhou1 1Department of Pharmacy, Renmin Hospital of Wuhan University, Wuhan, Hubei 430060, People’s Republic of China; 2Department of Pharmacy, Dongfeng Hospital, Hubei University of Medicine, Shiyan, Hubei 442008, People’s Republic of China; 3Department of Endocrinology, Renmin Hospital of Wuhan University, Wuhan, Hubei 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Benhong ZhouDepartment of Pharmacy, Renmin Hospital of Wuhan University, Wuhan, Hubei 430060, People’s Republic of ChinaTel +86 15335898431Email benhongzh@whu.edu.cnBackground and Objective: The combination of naloxone hydrochloride (NH) and fentanyl citrate (FC) in patient-controlled analgesia (PCA) is examined to reduce the risk of opioid-induced nausea and vomiting. However, there are no such commercially available drug mixtures, and there is also no published evidence on the compatibility and stability of NH and FC. Thus, the primary purpose of the current research is to investigate the physical compatibility and chemical stability of NH when mixed with FC over a 72-h period in a 0.9% sodium chloride injection solution for PCA administration under storage at 4°C and 25°C.Methods: Test solutions of 20 μg/mL FC and 4 μg/mL NH were prepared and stored in polyvinyl chloride (PVC) bags or glass bottles with a 0.9% sodium chloride injection solution as the diluent. During the 72-h storage period at 4°C or 25°C without light protection, the concentrations of the test drugs were assayed via high-performance liquid chromatography (HPLC), and the physical compatibility was determined with the naked eye. Furthermore, pH measurement of each sample was also performed with a pH meter.Results: The percentages of the initial concentrations of FC and NH in the various solutions were maintained at a minimum of 98% over the 72-h study period. All of the mixtures remained clear and colourless throughout the observation period, and no precipitation or turbidity was observed in any of the batches.Conclusion: The 20 μg/mL FC test solution was physically compatible and chemically stable with the 4 μg/mL NH test solution when stored at 4°C or 25°C in PVC bags or glass bottles containing the 0.9% sodium chloride injection solution.Keywords: fentanyl, naloxone, patient-controlled analgesia, 0.9% sodium chloride, drug stability